Factors influencing of performance management toward Syarikat Bekalan Air Selangor Berhad (SYABAS) / Haslina Mohamed Nuddin - Mohamed Nuddin, Haslina (Faculty of Business and Management, 2010)
The researcher has decided to focus on the “Factors Influencing of Performance Management Toward Syarikat Bekalan Air Selangor Berhad (SYABAS). The researcher is going to study further more on the performance management on SYABAS in order to investigate whether or not these factors have a relationship with the performance management on the company. These factors include human capital, appointed contractors, development and training and rewards. The survey is conducted at organization in SYABAS Head Quarter which is Kuala Lumpur area. The sample size for this study is 50 of employees Department of Management especially internal operation and maintenance. Data obtained using two methods that are primary and secondary data. Respondent are required to answer the questionnaires that contain element that potentially have relationship with performance management on the Company. Data are analyzed using Reliability Test, Frequency and Descriptive Statistic through SPSS Program. Based on SPSS Program a clear findings and result is observed. The findings showed the factor that significant relationship with performance management on SYABAS human capital and appointed contractors. Based on these factors, the company should highlight that human capital and appointed contractors are very important to the Company in order to increase performance management on the Company. Recommendation and suggestions are put on how to improve and increase the performance management on SYABAS regarding to others factor.